The Doctrine of Seventh-day Adventist Church on‎ Food According to Ellen G. White - Asep Awaludin; Jamal Jamal; Muttaqin Muttaqin (Universitas Darussalam Gontor, 2018)
This study aims to understand the concept of food according to Ellen G White ‎based on the teachings of Seventh-day Adventist Church. The object of this ‎research is all about healthy lifestyles following Old Testament as a reference. ‎Ellen recommends her pupils to consume healthy and nutritious food, as well as ‎prohibits consuming foods that can disturb their condition. In order to achieve an ‎objective mentioned above, this research utlizes a theological-normative approach; ‎with an intention to reveal Ellen’s interpretation for the doctrine of food regarding ‎the authenticity values founded within Old Testament. Accordingly, both descriptive ‎and analysis method are executed to analyze this topic altogether with religious ‎notions and the ideas of nutritionists. This research results a number of ‎conclusions: First, the types of food nutrients are good elements for health of ‎human body in accordance with the Biblical rules are: fruits, grains, vegetables, ‎and any other crops. Second, Ellen also permitted another type of meals besides ‎what has already mentioned above such as bread, cake, egg, milk, cheese, and fruit ‎juice because these dishes sanify and affect good behavior for human. Moreover, ‎those foods are also easily to be obtained among the poors. The types of foods ‎prohibited by White, however, are tea, coffee, meat, tobacco, and alcoholic ‎beverages, for instances. The reason behind it is that those meals are derived from ‎animal nutrients and possibly causing illness to the body.Those diseases are: ‎tuberculosis, cancer, and complications toward entire organs of human body. The ‎tea and coffe, in the other hands, affect headache, wakefulness, heart palpitation, ‎indigestion, trembling, and even leads to deviate behavior.